Methylene insertion into an Fe2S2 cluster: formation of a thiolate-bridged diiron complex containing an Fe–CH2–S moiety. Issue 93 (6th November 2018) - Su, Linan; Yang, Dawei; Zhang, Yixin; Wang, Baomin; Qu, Jingping
Abstract : Cleavage of both C−Cl bonds in CH2 Cl2 by a reduced iron–sulfur cluster induced unexpected methylene insertion into the Fe–S bond. Abstract : Reduction of a thiolate-bridged Fe II Fe III complex leads to the cleavage of an Fe–S bond by the insertion of the methylene unit from CH2 Cl2 to give a neutral Fe II Fe III complex with a novel Fe–CH2 –S fragment. The structural and electrochemical differences of the alkylated and the non-alkylated Fe2 S2 complexes are also examined.